Urological complications following unstented pediatric renal transplantation. (20th August 2017) - Maison, Patrick Opoku Manu; Smit, Shaun; McCulloch, Mignon; Gajjar, Priya; Nourse, Peter; Thomson, Dave; Muller, Elmi; Millar, Alastair; Numanoglu, Alp; Kahn, Delawir; Lazarus, John
Abstract: Urological complications which develop post‐renal transplantation can be associated with significant morbidity especially in children. We evaluated the occurrence and management of all urological complications in a series of unstented pediatric renal transplants in a tertiary pediatric hospital. We reviewed the medical records of children who underwent unstented renal transplant between January 1996 and December 2014. Postoperative urological complications and the outcomes of their management were analyzed. A total of 160 unstented renal transplants were performed, and 32 urological complications were noted in 29 transplants (18%). There were 20 boys and nine girls with an age range of 2.5 years to 18.4 years. Nine (31%) of these patients had LUTD. The most common complication was VUR occurring in 17 patients (10.6%). Urine leaks occurred in six patients (3.8%) and ureteric obstruction in six patients (3.8%), and three patients (1.9%) had unexplained hydronephrosis. Loss of graft occurred in three patients (1.9%), and one patient died from sepsis post‐uretero‐ureterostomy. Patients with LUTD had more urological complications ( P = .037). Unstenting is feasible in most pediatric renal transplants. LUTD is associated with a higher incidence of urological complications, especially VUR.